2011
DOI: 10.1186/1741-7015-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism in people admitted to hospital with selected immune-mediated diseases: record-linkage study

Abstract: BackgroundVenous thromboembolism (VTE) is a common complication during and after a hospital admission. Although it is mainly considered a complication of surgery, it often occurs in people who have not undergone surgery, with recent evidence suggesting that immune-mediated diseases may play a role in VTE risk. We, therefore, decided to study the risk of deep vein thrombosis (DVT) and pulmonary embolism (PE) in people admitted to hospital with a range of immune-mediated diseases.MethodsWe analysed databases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
354
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(384 citation statements)
references
References 21 publications
21
354
2
7
Order By: Relevance
“…A few populationbased epidemiological studies have been performed in Europe and the United States. Ramagopalan 8 Zöller et al reported a study on risk of PE in patients with autoimmune disease from Sweden. The MigMed2 database containing information about all registered residents of Sweden from 1964-2008 was used.…”
Section: Epidemiology Of Vte In Systemic Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few populationbased epidemiological studies have been performed in Europe and the United States. Ramagopalan 8 Zöller et al reported a study on risk of PE in patients with autoimmune disease from Sweden. The MigMed2 database containing information about all registered residents of Sweden from 1964-2008 was used.…”
Section: Epidemiology Of Vte In Systemic Autoimmune Diseasesmentioning
confidence: 99%
“…5 Recent large-scale epidemiological studies have highlighted systemic autoimmune diseases as a risk factor for VTE. [6][7][8] This article aims to touch upon VTE among patients with systemic autoimmune diseases and to discuss the occurrence of this condition among patients with primary systemic vasculitides (PSV). Since the literature on VTE in patients with PSV is scarce, mechanisms pertaining to other systemic autoimmune diseases have been hypothetically extrapolated to patients with PSV.…”
Section: Introductionmentioning
confidence: 99%
“…deep vein thrombosis (DVT) and its complication pulmonary embolism (PE), because they are reported to have hyperhomocysteinaemia, low levels of K-vitamin-dependent anticoagulant proteins, and increased levels of thrombin-activatable fibrinolysis inhibitor (Halfdanarson et al, 2007). There are several case reports regarding VTE occurrence in CD patients (Daum et al, 2009;Halfdanarson et al, 2007), but observational studies present conflicting results and may have been confounded by medication use and several comorbidities (Ludvigsson et al, 2007;Miehsler et al, 2004;Ramagopalan et al, 2011).…”
mentioning
confidence: 99%
“…Prior studies have been smaller in size or descriptive [5,26,27], done in the context of specific hyper coagulable states [28,29], or with a design that excluded secondary AIHA patients or lacked anon-AIHA cohort matched for relevant AIHA risk factors [14][15][16][17]19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies included the meta-analysis were limited in the extent to which they matched their AIHA and non-AIHA cohorts. Yusuf, et al matched their non-AIHA cohort according to age and gender alone [14], while the other three studies required their non-AIHA cohort to only lack a diagnosis of AIHA [15][16][17].…”
Section: Introductionmentioning
confidence: 99%